1997
DOI: 10.1063/1.119809
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional narrowing of Ge on Si(100) coherent island quantum dot size distributions

Abstract: The normalized width=standard deviation of island radius/mean island radius (σr/〈r〉) of molecular beam epitaxy grown Ge on Si(100) coherent island quantum dot size distributions is analyzed for various deposition conditions. It is found that this width decreases as substrate temperature increases independent of deposition flux. This result is interpreted in the context of models which suppose that the energy barrier for edge atom detachment decreases with island size. The faster diffusion kinetics at higher gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Our observations indicate that the density of dislocated clusters can be minimized by limiting the Ge coverage for any substrate temperature/deposition rate pair. We have also observed that higher substrate temperatures result in narrower island size distributions [10,11,36], an effect which has been attributed to the existence of a kinetic attachment barrier that increases with island size [37,38]. Growth at these higher temperatures is accompanied by increased Si interdiffusion as well as the formation of trenches at some of the cluster bases.…”
Section: Discussionmentioning
confidence: 84%
“…Our observations indicate that the density of dislocated clusters can be minimized by limiting the Ge coverage for any substrate temperature/deposition rate pair. We have also observed that higher substrate temperatures result in narrower island size distributions [10,11,36], an effect which has been attributed to the existence of a kinetic attachment barrier that increases with island size [37,38]. Growth at these higher temperatures is accompanied by increased Si interdiffusion as well as the formation of trenches at some of the cluster bases.…”
Section: Discussionmentioning
confidence: 84%
“…In several cases, the islands spontaneously form with a surprisingly narrow size distribution (Drucker and Chapparro, 1997;Goryll et al, 1997;Kamins et al, 1997;Kobayashi et al, 1996;Leonard et al, 1993;Medeiros-Ribeiro et al, 1998;Moison et al, 1994;Ponchet et al, 1995;Reaves et al, 1996;Xin et al, 1996). These narrow size distributions, although very convenient for device applications, are not well understood.…”
Section: Introductionmentioning
confidence: 96%
“…Similar difficulty in controlling Ge dot structures was observed when the substrate temperature is changed during the Ge deposition [5,14].…”
Section: (D)mentioning
confidence: 80%